Survey of using grasshopper algorithm - Osman, Hanaa Mohammed; Alsawaf, Rahma Saleem; Hammo, Asma'a Yaseen (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The metaheuristic optimization algorithm is used to explain a large region solution space. One of these algorithms is a grasshopper which divides the search process into exploitation and exploration. This article focuses on research efforts directed at gaining a clear understanding of the behavior of grasshoppers and it is using optimization algorithms. It is concluded that the benefits have been effective in answering global unrestricted and restricted optimization issues, easy development, high accuracy, and obtaining a good solution. However, the disadvantages of the GOA algorithm are simple to fall into local optimum and slow convergence speed.